(untitled) (Annual of the Faculty of Philosophy in Skopje, 2015)
Today’s is increasingly visible infiltration of international terrorist groups in the world financial flows and the international monetary system. This paper analyzes objectives of the activity of international terrorist organizations which are moving from the psychological effect of creating fear and uncertainty to devastating effect on the international economy and the devastating environmental consequences. Given the ability to produce catastrophic consequences for the world economy, to destabilize global political, financial and monetary relations, to destabilize global capital flows and investments, jeopardizing global security, begins the transformation of terrorism in partner in the new global conflict.